Diabetes mellitus and congenital proximal femur hypoplasia: is there a link or association - Mervat Essam; Ahmed Yamani (SpringerOpen, 2017)
We present a case of congenital short femur with scleredema Diabeticorum (SD) in a patient with diabetic neuropathy with unusual skin lesion distribution. Gait symptoms progressively worsened. The atypical distribution of the skin lesions is quite unusual. This case express rare complications of diabetes mellitus, the maternal diabetes which had disrupted in part the development of skeletal system of the offspring who in turn developed a rare dermatologic complications i.e. scleredema Diabeticorum (SD). This case will leave inedible memory for every diabetologist not to miss the skeletal and dermatologic manifestations of DM. The combination of this congenital proximal femoral hypoplasia with complicating diabetes make the question if there is a link with similar genetic predilection or just an association.